دور النسب المالية في التنبؤ بالتعثر المالي " دراسة تطبيقية على عينة من المؤسسات الصغيرة والمتوسطة الجزائرية خلال الفترة (2009- 2014 ) " - شربي, محمد الأمين; طباخ, إلهام (جامعة الوادي - University of Eloued, 2018)
This study aims to obtain the best collection of financial ratios from the financial list which can be used to forecast the establishment whether their failure or their success through using the statistics style which known by the discrimination factorial analsis “L’AFD” to build a model predictable about the financial failure, the sample contains 54 failed establishments whether small or normal enterprise, including 22 filed establishment but the rest are good, by taking into account the financial ratios of the sample under study (2009-2014). Two financial ratios from 18 indicate their ability to distinguish between the failed and good establishment. The ratios of profit before taxation to the total debts, beside the ratios are able to build a predictable model with quality of granding 76.2%
The role of financial ratios to predict financial distress A case study of sample small and medium enterprises Algerians in the period
مقال
Keywords: مخطر التعثر، نسب مالية، تنبؤ، تحليل عاملي تمييزي.; the risk of failure, failure ratios, forecast, analysis, factorial discrimination.